Short-term exercise affects cardiac function ex vivo partially via changes in calcium channel levels, without influencing hypoxia sensitivity - Uurasmaa Tytti-Maria; Streng Tomi; Alkio Milla; Heinonen Ilkka; Anttila Katja (SPRINGER, 2025)
Exercise is known to improve cardiac recovery following coronary occlusion. However, whether short-term exercise can improve cardiac function and hypoxia tolerance ex vivo independent of reperfusion injury and the possible role of calcium channels in improved hypoxia tolerance remains unknown. Therefore, in the current study, heart function was measured ex vivo using the Langendorff method at different oxygen levels after a 4-week voluntary wheel-running regimen in trained and untrained male mice (C57Bl/6NCrl). The levels of cardiac Ca2+-channels: L-type Ca2+-channel (CACNA1C), ryanodine receptor (RyR-2), sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA2), and sodium-calcium exchanger were measured using western blot. Trained mice displayed lower cardiac afterload pressure generation capacity (rate and amplitude), but unaltered hypoxia tolerance when compared to untrained mice with similar heart rates. The level of CACNA1C positively correlated with the pressure generation rate and amplitude. Furthermore, the CACNA1C-RYR-2 ratio also positively correlated with the pressure generation rate. While the 4-week training period was not enough to alter the intrinsic cardiac hypoxia tolerance, interestingly it decreased pressure generation capacity and slowed pressure decreasing capacity in the mouse hearts ex vivo. This reduction in pressure generation rate could be linked to the level of channel proteins in sarcolemmal Ca2+-cycling in trained mice. However, the Ca(2+-)channel levels did not differ significantly between the groups, and thus, the level of calcium channels cannot fully explain all the functional alterations, despite the detected correlations. Therefore, additional studies are warranted to reveal further mechanisms that contribute to the reduced intrinsic capacity for pressure production in trained mouse hearts.